Walt Whitman the song of himself - Loving, Jerome 1941- (University of California Press, 1999)
A biography of Walt Whitman, the 19th century writer hailed as the father of American poetry. It traces his life as a printer and journalist, before his self-published collection, Leaves of Grass, brought him fame. He was a great promoter, going so far as to write his own book reviews for newspapers. As a poet, he rejected regular meter and rhyme in favor of free verse and blazed the trail as a writer of erotica.